Dispersion model of NOx emissions from a liquefied natural gas facility - Türkyılmaz, İlker; Kuzu, S. Levent (Environmental Research and Technology, 2024)
Natural gas used widely in terms of energy production. Energy production is among the most prominent sectors of humankind. Combustion processes inevitably produces air pollutants. The major pollutant during a combustion process is nitrogen oxide emissions. The term of nitrogen oxides primarily include nitrogen monoxide and nitrogen dioxide. These pollutants are generated regardless of the fuel content since air composition itself is the major source for these pollutants. It is possible to calculate emissions through the activity data and emission factors. Calculation of emissions is not enough for an environmental assessment. The impact of pollutants on human health relies on their concentration in the atmosphere. In order to determine their concentrations several modelling practices are developed. In this study, AERMOD used for modelling purpose of NOx emissions from a liquefied natural gas facility. It was observed that the pollutants were dispersed mostly towards south-southwest of the facility, where Marmaraereğlisi district is located. Although the pollutants transported directly to the settlement, the concentrations remained limited. During operation conditions, the highest daily NOx concentration was 1.7 μg/m3 and the highest annual concentration was 0.1 μg/m3. At maximum operating conditions, the highest daily NOx concentration was 16.2 μg/m3 and the highest annual concentration was 2.5 μg/m3. At minimum operating conditions, the highest daily NOx concentration was 1.1 μg/m3 and the highest annual concentration was 0.2 μg/m3.
Keywords: Air Pollution Processes and Air Quality Measurement; Liquefied natural gas; emissions; dispersion model; Aermod; Hava Kirliliği Süreçleri ve Hava Kalitesi Ölçümü